THE IMPORTANCE OF INTERNAL AUDIT IN THE CORPORATE GOVERNANCE SYSTEM - Pulatova Marina Baxodirovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Currently, the emergence of risks associated with fraud at enterprises is aimed at the role and mechanism of the internal audit service in order to meet the needs of internal and external users for reliable, objective information. The importance of ongoing research lies in the fact that it increases the reliability of the results of the internal audit service, ensures the independence of the auditor and increases its objectivity and reliability.